Implementation of Compulsory Defence In The Indonesian Criminal Justice System: A Normative Analysis and Study of Court Decisions - Kayla Andini Putri; Kuswandi (Indonesian Journal of Law and Justice, 2025)
Necessary defence is a criminal defence that plays an important role in Indonesian criminal law, especially amid increasing public vulnerability to the threat of crime. Although it is regulated in Article 49 of the Criminal Code and reinforced by Article 34 of Law Number 1 of 2023, its application in practice still faces various problems. The main problem lies in law enforcement officials' assessment of the elements of forced defence, such as proportionality, immediacy, inability to avoid, and the psychological condition of the perpetrator, which often leads to the criminalisation of defensive actions that should be lawful. This study uses a normative juridical approach with case studies of Donggala District Court Decision Number 32/Pid.B/2021, Sinjai District Court Decision Number 101/Pid.B/2024, and the Amaq Sinta case to examine the consistency of the application of forced defence in judicial practice. The results of the study show that the application of noodweer is highly dependent on the objectivity of investigators and the thoroughness of judges in understanding the factual context and the dynamics of the threat faced by the perpetrator. Differences in understanding among officials often create a gap between legal norms and law enforcement practices. Therefore, standardised interpretation, clear technical guidelines, and capacity building for officials are needed so that self-defence can realise substantive justice and effective protection of the right to life and safety of individuals.